Importance of the analysis of flora and fauna to understand the «construction» of the multiple human-sacred-nature combinations in ancient Peru - García Escudero, María del Carmen (2022)
The author analyzes the information in the book Dioses y Hombres de Huarochirí, focusing mainly on the flora and fauna and their relationship with the so-called “current order”. How it is “built”, aspects of the flora and fauna are merged, for example, to articulate a human being in its “totality”, an anthropomorphic being, semi-divine beings, etc. Following our research proposal, we will demonstrate, once again, that the history of “ancient Peru” has been minimized and that there are multiple objectives still to be addressed. In this way we break with the established monolithic projects of gods structured with colonial sources derived from analysis with objectives already closed in outdated and repetitive conclusions. We present an analysis of the multiple dimensions of the study objective, and we focus our research to try to understand, not repeat colonial interpretations, which are very useful, but they are still interpretations and adaptations for the neophyte. We anticipate the reader that flora and fauna are symbiotically linked with men, gods, huacas, proto-men and healers. This can be part of a god, a huaca or a man, it can be a receptacle during the metamorphosis of a man into a bird, and other characteristics that we will analyze.